Mathematical Understanding and Proving Abilities: Experiment With Undergraduate Student By Using Modified Moore Learning Approach - Maya, Rippi; Sumarmo, Utari (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
This paper reports findings of Ã‚Â a Ã‚Â post test experimental control groupÃ‚Â design conducted to investigate the role of modified Moore learningÃ‚Â approach Ã‚Â on improving studentsÃ¢â‚¬â„¢ mathematical understanding andÃ‚Â proving abilities. Subject of study were 56 undergradute students of oneÃ‚Â state university in Bandung, who took advanced abstract algebraÃ‚Â course. Instrument of study were a set test of mathematicalÃ‚Â understanding ability, a set test of mathematical proving ability, and aÃ‚Â set of studentsÃ¢â‚¬â„¢ opinion scale on modified Moore learning approach.Ã‚Â Data were analyzed by using two path ANOVA. The study found thatÃ‚Â proof construction process was more difficult than mathematicalÃ‚Â understanding Ã‚Â task Ã‚Â for all students, and students still posed someÃ‚Â difficulties on constructing mathematical proof task. Ã‚Â The study alsoÃ‚Â found there were not differences Ã‚Â between studentsÃ¢â‚¬â„¢ Ã‚Â abilities onÃ‚Â mathematical understanding and on proving abilities of Ã‚Â the bothÃ‚Â classes, and both abilities were classified as mediocre. However, inÃ‚Â modified Moore learning approach class there were more students whoÃ‚Â got above average grades on mathematical understanding than those ofÃ‚Â conventional class. Moreover, students performed positive Ã‚Â opinionÃ‚Â toward Ã‚Â modified Moore learning approach. They Ã‚Â were Ã‚Â active inÃ‚Â questioning and solving problems, and in explaining their works inÃ‚Â front of class as well, while students of conventional teaching preferedÃ‚Â to listen to lecturerÃ¢â‚¬â„¢s explanation. The study also found that there wasÃ‚Â no interaction between learning approach and studentsÃ¢â‚¬â„¢ priorÃ‚Â mathematics ability on mathematical understanding and provingÃ‚Â abilities, Ã‚Â but Ã‚Â there were Ã‚Â quite strong Ã‚Â association between studentsÃ¢â‚¬â„¢Ã‚Â mathematical understanding and proving abilities.Keywords: Ã‚Â modified Moore learning approach, mathematicalÃ‚Â understanding ability, mathematical proving ability.Ã‚Â DOI: http://dx.doi.org/10.22342/jme.2.2.751.231-250